Targeting myeloid signalling pathways to unleash T cells - Michl, Patrick; Krug, Sebastian (Gut, 2023)
Unlike in numerous other tumors, the efficacy of checkpoint inhibitor-based immunotherapies in colorectal cancer (CRC) is restricted to the small subgroup of patients with mismatch repair-deficiency or microsatellite instability accounting for only a small minority of cases.1 The vast majority of patients with advanced, microsatellite-stable CRC, however, is currently resistant to checkpoint inhibitors and thus are not candidates for regimens containing antibodies targeting inhibitory immune checkpoint receptors. Therefore, it is an urgent unmet clinical need to explore new avenues to render microsatellite-stable CRCs immunologically ‘hot’ and thus susceptible to checkpoint inhibitor-based therapies. - - In many cancers including CRC, resistance to immunotherapy is mainly mediated by the tumour immune microenvironment. Particularly, infiltrating immune cells such as tumour-associated macrophages (TAMs) can polarise into a tumour-promoting, anti-inflammatory M2 phenotype that mediates T cell exhaustion thus rendering the tumour immunologically ‘cold’.2 To date, it remains largely unresolved how to effectively reverse T cell exhaustion in these tumours. Given the intense immunosuppressive impact of M2-polarised TAM on T cells, signalling pathways in M2-TAMs represent an interesting avenue to indirectly enhance T cell function.2 - - In this context, in GUT , Li et al 3 identified a promising myeloid signalling target: The membrane spanning four domains A4A (MS4A4A) protein that …